Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match Berbasis Problem Solving dan Minat Belajar terhadap Hasil Belajar Ekonomi (Studi Kuasi Eksperimen Faktorial 2x2 pada Siswa SMA Negeri 36 Jakarta) - Desi Wulandari; Ari Saptono; Agus Wibowo (Educational Journal, 2026)
This study was motivated by low student economics learning outcomes caused by the dominance of teacher-centered conventional learning models and low student learning interest. This study aims to examine the effect of a Problem Solving-based Make a Match cooperative learning model and learning interest on the economics learning outcomes of Grade XI students at SMAN 36 Jakarta. A quantitative method with a quasi-experimental approach using a 2x2 factorial design was employed. The sample comprised 72 students selected through purposive sampling. Data were collected using a 25-item multiple-choice test for learning outcomes and a 25-item Likert-scale questionnaire for learning interest. Data were analyzed using descriptive statistics and Two-Way ANOVA via IBM SPSS version 26. The findings revealed: (1) a significant difference in economics learning outcomes between students taught with the Problem Solving-based Make a Match model and the conventional model; (2) a significant difference in learning outcomes between students with high and low learning interest; and (3) a significant interaction between the learning model and learning interest on economics learning outcomes. In conclusion, the Problem Solving-based Make a Match cooperative learning model effectively improves students' economics learning outcomes independently, regardless of their level of learning interest.